A multiview-based automatic method for 3D fracture line extraction. (August 2022) - Liao, Sheng-hui; Peng, Chun-lin; Liu, Shu; Xiong, Chao; Liu, Li-hong
Highlights: Computer-assisted automatic 3D fracture line extraction is realized. The novel centerline extraction method is very fast and robust. Fast automatic fracture mapping helps doctors locate fracture. Our method can extract fracture lines in seconds. Abstract: The 3D fracture line is the centerline of the crack region on the surface of the bone that can effectively help orthopedists understand fracture distribution and aid in fracture treatment. However, no effective automatic extraction method exists, and fracture lines still require manual work. This paper develops an efficient automatic method for fracture line extraction from multiple reassembled fragments. In the initial step, we propose a multiview sampling strategy based on spherical uniform viewpoints, which uses off-screen rendering to sample fragments from multiple viewpoints. Markers are generated from the samples and integrated from all viewpoints. Then, we use a new point-based centerline extraction algorithm to merge markers and extract the fracture lines. Finally, we propose a normal-based fracture line mapping method to quickly and reliably map fracture lines to the surface of a standard bone template. Experiments indicate that our method can extract fracture lines from six common complex fragments within 3 s. Through multiview experiments, we select 30 viewpoints so that most template mesh triangles corresponding to the six fragments can be simultaneously observed from at least 2 viewpoints. Additionally, anti-noise experiments show that the proposed method can handle high-noise and cancellous fragments reliably. For complex fragments, our method is still applicable, has strong practicality, and can effectively help doctors save time.